2016
DOI: 10.1016/j.apsusc.2016.03.161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis by anodic-spark deposition of Ca- and P-containing films on pure titanium and their biological response

Abstract: The purpose of this work is to characterize the anodized layers formed on titanium by anodicspark deposition in a electrolyte containing Ca and P ions, Ca3(PO4)2, studied for the first time. The oxidation experiments were performed at different periods of time and using different concentrations of electrolyte. The influence of the process parameters (time of electrolysis and electrolyte concentration) on the surface morphology and chemical composition of the anodized layers was studied. It has been found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Regarding the anodic treated samples, the decrease on OCP with immersion time may be related to partial dissolution of the anodic film. Banakh et al [35] evaluated the response of anodic oxide layers containing Ca and P by immersion in a simulated body fluid and reported that Ca and P content in the anodic layers decreased after 14 days of immersion. Moreover, Ca dissolution occurs at higher rates than P. However, during the immersion period, the anodic treated samples presented more positive values than untreated Ti indicating a lower tendency to corrosion.…”
Section: Open Circuit Potential Evolution Versus Immersion Timementioning
confidence: 99%
“…Regarding the anodic treated samples, the decrease on OCP with immersion time may be related to partial dissolution of the anodic film. Banakh et al [35] evaluated the response of anodic oxide layers containing Ca and P by immersion in a simulated body fluid and reported that Ca and P content in the anodic layers decreased after 14 days of immersion. Moreover, Ca dissolution occurs at higher rates than P. However, during the immersion period, the anodic treated samples presented more positive values than untreated Ti indicating a lower tendency to corrosion.…”
Section: Open Circuit Potential Evolution Versus Immersion Timementioning
confidence: 99%
“…Biological assays were detailed previously [13,14]. Briefly, human osteoblasts like cells HOS (ATCC ® CRL1543 TM ) (HOBs) were grown on several anodized samples.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…With a mixed electrolyte including both silicates and phosphates, Li et al [3] showed in particular the simultaneous incorporation of both compounds. Furthermore, Banakh et al (11] demonstrated that the incorporation of phosphate and calcium, from the electrolyte {KOH + Ca 3 (P0 4 )i}, was preferentially carried out in the coating amorphous phase. Khorasanian et al [12] have studied a low cost and original electrolyte composed of sodium silicate, hydrogen peroxide, starch and sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%